2009
DOI: 10.1128/aem.00436-09
|View full text |Cite
|
Sign up to set email alerts
|

Improved Detection of F-Specific RNA Coliphages in Fecal Material by Extraction and Polyethylene Glycol Precipitation

Abstract: Male-specific RNA coliphages (F-RNA coliphages) have been proposed as a potential viral indicator of fecal contamination in water and foods because they are easy to culture and are a normal component of the mammalian gut flora. F-RNA coliphage plaque numbers are typically obtained by directly plating a 10-fold dilution of 1 g of fecal material, but the numbers of F-RNA coliphages shed by animals and humans may be too low for direct enumeration. Therefore, the sensitivity of detecting F-RNA coliphages in fecal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…To determine host specificity of GB-124 phages, a total of 264 animal faecal samples from 14 different species (collected in the northeastern US) were analysed for GB-124 phages, along with F-RNA and somatic coliphages (Table 1). F-RNA coliphages were detected in both dog faeces (1Á90 AE 0Á09 PFU g À1 dry weight [dw]) and cattle manure slurry (1Á74 AE 0Á17 PFU g À1 dw), whereas somatic coliphages were detected in the majority of animal faecal samples, ranging from 1Á75 to 4Á78 PFU g À1 dw of faeces, which is comparable to previous reports for nonhuman faecal sources (Cole et al 2003;Jones and Johns 2009;Muniesa et al 2012). GB-124 phages, however, were not detected in any of the nonhuman faecal samples analysed (Table 1), which is consistent with earlier findings from the EU (Ebdon et al 2007Ogilvie et al 2012).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…To determine host specificity of GB-124 phages, a total of 264 animal faecal samples from 14 different species (collected in the northeastern US) were analysed for GB-124 phages, along with F-RNA and somatic coliphages (Table 1). F-RNA coliphages were detected in both dog faeces (1Á90 AE 0Á09 PFU g À1 dry weight [dw]) and cattle manure slurry (1Á74 AE 0Á17 PFU g À1 dw), whereas somatic coliphages were detected in the majority of animal faecal samples, ranging from 1Á75 to 4Á78 PFU g À1 dw of faeces, which is comparable to previous reports for nonhuman faecal sources (Cole et al 2003;Jones and Johns 2009;Muniesa et al 2012). GB-124 phages, however, were not detected in any of the nonhuman faecal samples analysed (Table 1), which is consistent with earlier findings from the EU (Ebdon et al 2007Ogilvie et al 2012).…”
Section: Resultssupporting
confidence: 84%
“…F‐RNA coliphages were detected in both dog faeces (1·90 ± 0·09 PFU g −1 dry weight [dw]) and cattle manure slurry (1·74 ± 0·17 PFU g −1 dw), whereas somatic coliphages were detected in the majority of animal faecal samples, ranging from 1·75 to 4·78 PFU g −1 dw of faeces, which is comparable to previous reports for nonhuman faecal sources (Cole et al . ; Jones and Johns ; Muniesa et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…Calci et al (1998) reported that more than 53% of chickens in their study shed < 10 pfu/g of male‐specific coliphages. Jones and Johns (2009) concluded that certain properties of coliphages prevent their full recovery from fecal samples. These investigators observed male‐specific coliphage nondetects ranging from 30 to 96% in fecal samples from pigs, cattle, and poultry.…”
Section: Discussionmentioning
confidence: 99%
“…These investigators observed male‐specific coliphage nondetects ranging from 30 to 96% in fecal samples from pigs, cattle, and poultry. Jones and Johns (2009) think the 1 g of fecal material used in the coliphage enumeration process is insufficient. Male‐specific coliphages were detected in only 9 of 25 fecal samples when the sample size was 1 g; however, when the sample size was increased to 10 g, male‐specific coliphages were detected in 16 of 25 samples.…”
Section: Discussionmentioning
confidence: 99%
“…Different rates of survival at different temperatures for subgroups of F-specific coliphages have been reported in surface water (27,30,33,34). In addition, the numbers and shedding frequency of F-specific coliphages shed by individual hosts can be highly variable, which can result in variability in detection and density in surface waters when fecal contamination occurs (35)(36)(37).…”
mentioning
confidence: 99%